Morphological, cytological, biochemical and molecular characterization of Carica papaya L. Vasconcellea quercifolia (St. Hil.) Hieron and their intergeneric hybrid (The Philippine Journal of Crop Science, 2010)
The morphological, cytological, biochemical and molecular characteristics of Carica papaya x Vasconcellea quercifolia intergeneric hybrid were investigated to determine its true hybridity status. The morphological characteristics of C. papaya were completely different from those of V. quercifolia, a wild species. Two morphological characters, namely: the number of main leaf veins (7) and the leaf shape are intermediate of the two parents which are considered visual markers for the intergeneric hybrid. The intergeneric hybrid is resistant to papaya ringspot virus similar to V. quercifolia. Meiotic analysis showed normal chromosome behavior of the parents but several meiotic abnormalities like unpaired chromosomes, presence of laggards and unequal chromosome distribution were observed in the intergeneric hybrid resulting to low pollen fertility. Among the five enzyme systems analyzed, four isozyme loci were polymophic which could be also used as biochemical markers for the hybrid. In theSDH1 locus, the intergeneric hybrid had one slow moving band identical to the slow moving band of C. papaya and another band identical to the single band of V. quercifolia. In the PG/1 locus, the hybrid had a unique band which is faster than the fast moving band of C. papaya but slower than the fast moving band of V. quercifolia. Likewise, in the ADH1 locus, the intergeneric hybrid had also a unique band identical to V. quercifolia but with less intensity. Similarly, in the AMP1 locus, the hybrid had another unique band whose mobility is in between those of V. quercifolia but the intensity is similar to C. papaya. Hybridization of the total genomic DNA successfully differentiated the parents from their hybrids, and showed that the cultivated species, C. papaya and V. quercifolia showed that the intergeneric hybrid produced one-band ~1.64 kb identical to C. papaya and another two new bands i.e.~1.4 kb and ~1.2 kb not present in any of the parents which revealed true hybridity of the C. papaya x V. quercifolia intergeneric hybrid.